Investigating charge trapping in ferroelectric thin films through transient measurements - Lancaster, Suzanne; Lomenzo, Patrick D.; Engl, Moritz; Xu, Bohan; Mikolajick, Thomas; Schroeder, Uwe; Slesazeck, Stefan (Frontiers in Nanotechnology, 2022)
A measurement technique is presented to quantify the polarization loss in ferroelectric thin films as a function of delay time during the first 100s after switching. This technique can be used to investigate charge trapping in ferroelectric thin films by analyzing the magnitude and rate of polarization loss. Exemplary measurements have been performed on Hf0Zr0.5O2 (HZO) and HZO/Al2O3 films, as a function of pulse width and temperature. It is found that the competing effects of the depolarization field, internal bias field and charge trapping lead to a characteristic Gaussian dependence of the rate of polarization loss on the delay time. From this, a charge trapping and screening model could be identified which describes the dynamics of polarization loss on short timescales.